Validation of the Multidimensional Driving Style Inventory (MDSI) in professional drivers: How does it work in transportation workers? - Useche Hernández, Sergio Alejandro; Cendales, Boris; Aloonso, Francisco; Pastor, Juan C.; Montoro González, Luis (Transportation Research Part F: Traffic Psychology and Behaviour, 2020)
The Multidimensional Driving Style Inventory or MDSI constitutes, perhaps, the most relevant tool for measuring driving styles. Since its releasing in 2004, it has been applied worldwide to different samples of drivers, showing an important value and utility for road safety. However, empirical studies using the MDSI on professional drivers are scarce and, to the date, there is no validated version of the instrument in this workforce yet. Objectives: This study had two aims. First, to describe in detail the validation of the Taubman-Ben-Ari’s MDSI among professional drivers and, second, to test its convergent validity with other key relevant factors present in the work environment of this particular population: driving anger, job strain and occupational driving crashes. Method: The data used for this validation was gathered from a representative sample of 752 Colombian professional drivers and analyzed by means of competitive Confirmatory Factor Analyses (CFAs), assessing psychometric properties and obtaining an optimized structure for the instrument applied to active transportation workers. Results: The outcomes of this study suggest a clear factorial structure, adequate model fit, factorial weights, reliability and internal consistency, keeping the re-evaluated four-factor structure of the questionnaire: Reckless & Careless (F1); Anxious (F2); Angry & Hostile (F3); and Patient & Careful (F4). Conclusion: This applied research supports the hypothesis that the validated version of MDSI in professional drivers, together with further measures applied to other work environment factors, may play a relevant role in the improvement of driving safety and injury prevention for this vulnerable workforce from the perspective of occupational research in transportation.
Keywords: professional drivers; MDSI; validation; driving styles; personality; risky driving; work environment; Scopus; JCR